2022
DOI: 10.3389/fvets.2022.820304
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antibiofilm Activity of Selected Medicinal Plant Leaf Extracts Against Pathogens Implicated in Poultry Diseases

Abstract: Antimicrobial resistant poultry pathogens are responsible for treatment failure and economic losses, and can also be a source of resistant zoonotic infections representing a risk to human health. In 2006 the European Union banned the use of antibiotics as growth promoters in farm animals and other regions are likely to follow suit. Alternative products and strategies are sought to help maintain animal gut health to reduce the prevalence of pathogens in the food chain. The minimum inhibitory concentration (MIC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Olawuwo et al investigated the in vitro antibiofilm activity of Acalypha wilkesiana , Alchornea laxiflora , Ficus exasperata , Jatropha gossypiifolia , Morinda lucida , and Ocimum gratissimum plant extracts against poultry pathogens ( Aspergillus flavus , A. fumigatus , C. albicans , Campylobacter spp., Salmonella spp., E. coli , S. aureus, and Enterococcus faecalis ). All plant extracts showed effective biofilm inhibition of approximately >50% against the tested micro-organisms [ 160 ]. Fathi et al determined the antibiofilm potential of Malva sylvestris methanolic extract against some human pathogens, such as E. coli , S. aureus , P. aeruginosa , E. faecalis , and K. pneumoniae .…”
Section: Biofilm Controlling Compoundsmentioning
confidence: 99%
“…Olawuwo et al investigated the in vitro antibiofilm activity of Acalypha wilkesiana , Alchornea laxiflora , Ficus exasperata , Jatropha gossypiifolia , Morinda lucida , and Ocimum gratissimum plant extracts against poultry pathogens ( Aspergillus flavus , A. fumigatus , C. albicans , Campylobacter spp., Salmonella spp., E. coli , S. aureus, and Enterococcus faecalis ). All plant extracts showed effective biofilm inhibition of approximately >50% against the tested micro-organisms [ 160 ]. Fathi et al determined the antibiofilm potential of Malva sylvestris methanolic extract against some human pathogens, such as E. coli , S. aureus , P. aeruginosa , E. faecalis , and K. pneumoniae .…”
Section: Biofilm Controlling Compoundsmentioning
confidence: 99%
“…Numerous secondary metabolites from medicinal plants have anti-QS effects have been isolated such as cinnamaldehyde, flavanones, and flavonoids have been studied and demonstrated promising anti-QS activities specifically, inhibition of HAIand AI-2-medicated bioluminescence, restrict with QS detection and influence. 34 Olawuwo et al 35 observed a comparable observation in their determination of antibiofilm formation activity of the medicinal leaf extracts against bacterial biofilms.…”
Section: Discussionmentioning
confidence: 71%
“…It is now a crucial method for reducing the negative effects of stress on animals both domestically and overseas ( Liu and Yang, 2006 ). For the past several years, plant extracts has been increasingly used in poultry and mammals ( Olawuwo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%